2021
DOI: 10.1080/20008198.2021.1964197
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors, stressors, and symptoms of adjustment disorder during the COVID-19 pandemic – First results of the ESTSS COVID-19 pan-European ADJUST study

Abstract: Background:The COVID-19 pandemic exposes individuals to multiple stressors, such as quarantine, physical distancing, job loss, risk of infection, and loss of loved ones. Such a complex array of stressors potentially lead to symptoms of adjustment disorder. Objective: This cross-sectional exploratory study examined relationships between risk and protective factors, stressors, and symptoms of adjustment disorder during the first year of the COVID-19 pandemic. Methods: Data from the first wave of the European Soc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 58 publications
7
55
0
1
Order By: Relevance
“…Regarding COVID-19-related non-PTEs in general, the higher number of experienced stressors was not significantly related to the overall PTSD symptom intensity at the second measurement (r = 0.15, p = 0.08). Recent research on the correlation between pandemic-related stressors and mental health problems in the general population revealed higher levels of symptoms of adjustment disorder in those with a variety of COVID-19-related stressors [ 31 ]. Among veterans with an increased level of mental health suffering, different COVID-related stressors appeared to be the strongest risk factors for increased suicidality [ 9 ], increased distress [ 10 ], common mental disorders, and hazardous drinking [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COVID-19-related non-PTEs in general, the higher number of experienced stressors was not significantly related to the overall PTSD symptom intensity at the second measurement (r = 0.15, p = 0.08). Recent research on the correlation between pandemic-related stressors and mental health problems in the general population revealed higher levels of symptoms of adjustment disorder in those with a variety of COVID-19-related stressors [ 31 ]. Among veterans with an increased level of mental health suffering, different COVID-related stressors appeared to be the strongest risk factors for increased suicidality [ 9 ], increased distress [ 10 ], common mental disorders, and hazardous drinking [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of childhood abuse reported that preventive measures such as wearing protection over the mouth and nose reactivated trauma-related feelings such as powerless, helplessness, and limited self-determination; at the same time, some individuals with a history of childhood abuse felt safer than before the pandemic by keeping a distance and reducing physical contact (UKASK, 2020 ). In an ongoing international cohort study on symptoms of adjustment disorder (Lotzin, Krause, et al, 2021 ), restricted physical and social contacts, restricted leisure activities, work-related problems, and difficult housing conditions were associated with symptoms of adjustment disorders.…”
Section: Covid-19-related Mental Health Burden In Five European Count...mentioning
confidence: 97%
“…In an online cross-sectional study, in the convenience sample of 2088 respondents from the general population, high levels of symptoms for mental disorders were observed for anxiety (22.5%), depression (27.3%), post-traumatic stress disorder (PTSD) (12.1%), and adjustment disorder (36.0%) (Makhashvili et al, 2020 ). According to the findings of the ESTSS pan-European ADJUST study, out of the 11 countries participating in the study, Georgia and another Eastern European country (Lithuania) are experiencing the highest level of adjustment disorder symptoms (Lotzin, Krause, et al, 2021 ). However, no baseline pre-pandemic data are available for either of these countries to allow an insight into the extent to which the revealed picture can be attributed to the pandemic.…”
Section: Covid-19-related Mental Health Burden In Five European Count...mentioning
confidence: 99%
See 1 more Smart Citation
“…While interpreting the results of studies into the health impacts of the COVID-19 pandemic, one should consider the time of research and the successive waves of increase and decrease in the frequency of infections. From a long-term perspective, we can expect adaptation to new living conditions and an increased sense of safety after the introduction of mass vaccination [ 41 ], but also increasing symptoms of persistent anxiety, depression, and post-traumatic stress [ 42 ]. When interpersonal relationships are concerned, differences in the functioning of formal or informal relationships and sexual life can be expected between the first and subsequent months of the pandemic.…”
Section: Introductionmentioning
confidence: 99%